Tracheostomy as an Effort to Help Weaning Ventilated Obese Patient: A Case Report - Liliriawati Ananta Kahar; Diflayzer; Wiwi Monika Sari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The prevalence of tracheostomy in the ICU was performed in 10%-15% of patients. Tracheostomy is performed in patients with prolonged intubation. The most compelling indications for tracheostomy are acute respiratory failure with prolonged or expected prolonged duration of mechanical ventilation and failure to wean from a mechanical ventilator. Case presentation: A 60-year-old female patient came to the emergency room of Dr. M. Djamil General Hospital with decreased consciousness 2 days before admission. Vital signs showed Sopor consciousness, RR: 30 x/min, and BMI: 39 kg/m2. Thorax examination of bronchovesicular breath sounds, rhonchi +/+, wheezing +/+. The patient was intubated and put on a ventilator, and admitted to the ICU. A tracheostomy on day 5 was performed on the patient. The patient was able to be weaned from the ventilator and then admitted to the neurology ward on day 18. Conclusion: Tracheostomy can help weaning patients from mechanical ventilation. In this case, a severely obese patient can be weaned from the ventilator with a tracheostomy.